The Critical Role of Cultural Perception, Social Perception, and Social Safety on Altruistic Behaviour Among Bandung Residents: Resident Commitment and Life Satisfaction as Mediators - Hilmi Aulia Syarifah; Yadi Ernawadi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of cultural perception, social perception, social trust, and social safety on altruistic behavior through resident commitment and life satisfaction in the residents of the city of Bandung. This research is based on social exchange theory and subjective well-being theory to explain how citizens' perception of the social and cultural environment affects altruistic behavior. The study used a survey method with a quantitative approach involving 148 residents of the city of Bandung. Data was collected through questionnaires and analyzed using partial least squares structural equation modeling. The results showed that resident commitment was proven to mediate the influence of cultural perception, social perception, and social safety on altruistic behavior, while life satisfaction mediated the influence of social safety on altruistic behavior. The novelty of this research lies in the development of a conceptual model based on social exchange theory through the replacement of the dimensions of economic perception, environmental perception, and infrastructure perception with social trust and social safety, as well as the addition of life satisfaction as a mediating variable adopted from subjective well-being theory. The results of this research are expected to be an input for the Bandung City government to prioritize improving social safety, followed by cultural perception, then social perception to increase altruistic behavior of Bandung City residents. The findings of this study provide an opportunity to develop a conceptual model through testing variables and other theoretical perspectives to test factors that can increase altruistic behavior.